Developing PDPA-friendly moblie application: key takeaways for mobile apps developers - Zulhuda, Sonny (2015)
The convergence of the Internet and mobility is now the primary reason behind today’s digital inclusion. At the heart of this convergence is the rise of mobile applications (apps) which does not only define the dynamic of such convergence but also aim at increasing users’ personalised experiences. Naturally, the users’ need for such a customised services will be coupled with an increasing demand for privacy protection. A good and innovative product will never reach its maximum return if it is clouded with fear of breach of personal privacy. In this talk, the speaker will share with mobile apps developers or researchers trends and tips on the need to develop a privacy-friendly mobile apps taking into account both business needs and recent regulatory requirements in Malaysia, especially the Personal Data Protection Act 2010. At the end of the session, some practical takeaways will be shared for our mobile apps developers.